Evaluating Green Supply Chain Practices in Southeast Asia: A Text Mining Approach on Corporate Sustainability Reports - Anjani, Andi Dwi; Nur Aida, Iqlillah; Muhammad, Faishal (University of Science and Computer Technology, 2025)
This study addresses the growing imperative for environmentally responsible supply chain management in Southeast Asia and the challenges of assessing corporate sustainability disclosures. Although companies increasingly produce sustainability reports, the extent to which these documents reflect genuine green practices remains unclear. This research systematically evaluates how five major Southeast Asian firms, including Unilever SEA, Nestlé Indonesia, Indofood, Danone, and ThaiBev, articulate green supply chain initiatives in reports published between 2022 and 2023. Employing a qualitative exploratory design, the study integrates document analysis with text mining and thematic coding; approximately 33,000 words from the five reports were processed, yielding 1,300 occurrences of green supply chain terms categorized into three themes: eco-packaging, green logistics, and carbon tracking. The results reveal a pronounced imbalance: eco-packaging comprised 54 percent of keywords (n = 702), green logistics 29 percent (n = 377), and carbon tracking 17 percent (n = 221). Unilever’s 9,300-word report contained 350 mentions of eco-packaging, while Danone’s 5,900-word report featured 310; carbon tracking averaged under 45 references per report. The study introduces a replicable text mining framework for ESG disclosure analysis and underscores the need for more balanced reporting, including Scope 3 emissions data. Future mixed-method approaches that combine computational analysis with qualitative validation are advocated. The findings provide evidence for policymakers and investors to refine ESG guidelines and highlight the potential of computational tools to enhance corporate accountability in sustainability reporting